Inovasi Digitalisasi Pencatatan Keuangan Berbasis Aplikasi dalam Meningkatkan Literasi dan Numerasi Pengusaha Bawang Merah di Desa Telle Kabupaten Bone - Samsir, Andi Utari; Muktamar, Ahmad; Muliadi, Baso Nurul Ikram; Erviani S; Ancha, Salsabilla; Putria, Hasmulinda; Silalahi, Feri; Alma, Sulfina; Akram, Muh. Nauval; Samsinar, Samsinar (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service project aims to develop an innovative, application-based digital financial recording system to improve the financial literacy and numeracy of shallot entrepreneurs in Telle Village, Bone Regency. The main problems faced by the community are low levels of financial literacy and numeracy, as well as the continued use of unsystematic, manual recording in business activities. The method used is a participatory approach through Community Service Programs (KKN) with door-to-door mentoring, encompassing problem identification, innovation design, implementation, mentoring, and evaluation. The implementation utilized the Money Tracker application as a digital medium for financial recording. The results of the project indicate that the innovation implemented improved the community's ability to systematically record financial data, understand basic financial concepts, and improve the accuracy of transaction calculations. Furthermore, there was a significant increase in technology adoption and a shift in business management patterns from intuition-based to data-driven. The hands-on, hands-on approach and intensive mentoring proved effective in accelerating the community's adaptation to digital technology. Thus, this project contributes to the development of an integrative and contextual community service model and has the potential to be replicated in the MSME sector in other rural areas.